The Rates of Coexistence Metastases in Patients with Advanced Prostate Cancer in 68Ga-PSMA PET/CT: A Retrospective Analysis - Komek, Halil; Balci, Tansel Ansal (My University, 2019)
Objective: To determine the rate of metastasis and coexistence metastases in patients with advanced prostate cancer in gallium 68 -prostate specificmembrane antigen PET/CT (68Ga-PSMA PET/CT).Material and Method: A total of 234 consecutive patients with advanced prostate cancer who underwent 68Ga-PSMA PET/CT were included in thisretrospective study. Data on previous treatments, Gleason score, serum Prostate Specific Antigen (PSA) levels (ng/mL) and 68Ga-PSMA PET/CTfindings were recorded.Results: The mean age of the patients was 67.6 ± 8.5 years. Median PSA level was 21.7 (0.2-880) ng/ml. Pelvic (41%) and abdominal (30.3%) lymphnodes were the most commonly involved lymph nodes, while bone metastases were multimetastatic and bone carcinomatosis in 22.2% and 30.6% ofpatients, respectively. Other common distant organ metastases were lung (7.6%) and liver (7.2%) metastases. Level 1-4 lymph node positivity wasnoted in 29.4%, 33.3% and 6.8% of patients with liver metastasis, lung metastasis and seminal vesicle invasion, respectively. Concomitant lungmetastasis was evident in 41.1% of patients with liver metastasis, while lung or liver metastasis was evident in 13.6% of patients with seminal vesicleinvasion. Bone metastasis was evident in all patients with liver and lung metastasis, and in 65.9% of patients with seminal vesicle invasion.Conclusion: The findings of this study showed the value of 68Ga-PSMA PET/CT in detecting coexistence rate of metastases in advanced prostatecancer.
Keywords: Onkoloji